Districting and Government Overspending - Baqir, Reza (IMF Working Papers; Working Paper ;, 2001)
The common-pool problem is a central issue in the relationship between the political structure of jurisdictions and the size of public spending. Models predict that, other things being equal, greater political districting of a jurisdiction raises the scale of government. This paper presents new evidence on this and related predictions from a cross-section of city governments in the United States. The main finding is that one additional legislator is associated, on average, with 3 percent larger expenditures per capita. Evidence also suggests that forms of government with strong executives, particularly those with veto powers, break the link between districting and government size.